NHS jobs : using digital platforms to transform recruitment across the English & Welsh National Health Service - Thompson, Mark (Writer on economics), (SAGE knowledge. Cases., 2016)
Recruitment within the UK's National Health Service (NHS), Europe's largest employer, had become outdated, expensive and inefficient. Written by someone with first-hand involvement, this case study explores how a digital platform, NHS Jobs, was successfully introduced which completely transformed the recruitment activities of over 650 NHS employers across the country, saving the government D1bn and improving the service for both employers and applicants alike.